Exploration of Ionic Contamination for Groundwater in Some Irrigated Sites of Rajshahi Area (Journal of Environmental Science and Natural Resources, 2015)
Groundwater samples collected from 15 tube wells of six unions under Puthia upazila of Rajshahidistrict was evaluated their quality for irrigation usage in relation to soil properties and crop growth. Groundwater samples under test were slightly alkaline (pH = 7.10-7.34) in nature and were not problematic for crop production. As regards to TDS, allwater samples were classified as fresh water (TDS